2019
DOI: 10.20547/jms.2014.1906105
|View full text |Cite
|
Sign up to set email alerts
|

Managing Organizational Effectiveness through Talent Management and Career Development: The Mediating Role of Employee Engagement

Abstract: Considerable research has performed to link the individual development strategies into organizational performance, but less is known about the role of talent management and career development in enhancing the organizational effectiveness. In the current study, we investigate how talent management and career development direct or indirect effect organizational effectiveness. Moreover, the present study also pursues to test the mediating role of employee engagement in the association between talent management an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 18 publications
0
22
0
2
Order By: Relevance
“…The result finds support in previous research on employee engagement. For example, Ali et al (2019), from this study they found that there is a direct effect of TM practices and organizational effectiveness and also indirect effect of TM practices and organizational effectiveness through employee engagement. Kularetal (2008); Rama (2009) these researches supported that employee engagement is a mediating variable between employee development factors and organizational effectiveness.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The result finds support in previous research on employee engagement. For example, Ali et al (2019), from this study they found that there is a direct effect of TM practices and organizational effectiveness and also indirect effect of TM practices and organizational effectiveness through employee engagement. Kularetal (2008); Rama (2009) these researches supported that employee engagement is a mediating variable between employee development factors and organizational effectiveness.…”
Section: Discussionmentioning
confidence: 58%
“…Talent management system should apply to all human resource management functions. Having the right talent is the greatest benefit for every enterprise (Ali and Mehreen, 2019). The processes of talent management enhance the workforce output for the prosperity of the firm .…”
Section: Talent Management and Organizational Effectivenessmentioning
confidence: 99%
“…Talent management is an organization's ability to attract, hire and retain individuals with skills and competencies that will carter for the organization's present and future needs. Ali, Bashir, and Mehreen (2019) assert that talent management refers to the anticipation of required human capital for an organization and the planning to meet potential needs. Campbell and Hirsh (2013) view talent management as the best human resources in an organization whose performance highly influence the organization's overall performance.TM is the sourcing (finding talent), screening (sorting of qualified and unqualified applicants); selection (assessment/testing, interviewing, reference/background, checking, of applicants) on-boarding (offer generation/acceptance, badging/security, payroll, facilities; retention measures to keep the talent that contributes to the success of the organization); development (training growth, assignments); deployment (optimal assignment of staff to projects, lateral opportunities, promotions) and renewal of the workforce with analysis and planning as the adhesives, overarching ingredient (Brewster, Carely, Grobler, Holland, & Warnich, 2010).…”
Section: The Concept Of Talent Managementmentioning
confidence: 99%
“…This is not unconnected to the benefit of competitive advantage that an organization derives from having a talented workforce especially in this present era of globalization and stiff competition. Effective talent management policies and practices are those policies and practices that show commitment to employees, resulting in higher employee engagement and lower employee turnover, thereby impacting positively on organizational productivity and effectiveness (Ali et al, 2019;Beheshtifar, Nasab, & Moghadam, 2012). Ferreira, Neira, and Vieira (2012) affirm that talent management is the implementation of integrated strategies designed to raise employees' productivity by developing processes for attracting, developing, retaining, and utilizing people with the required skills and aptitude to meet the current and the future business needs.…”
Section: Benefits Of Talent Managementmentioning
confidence: 99%
See 1 more Smart Citation